1998
DOI: 10.1074/jbc.273.2.705
|View full text |Cite
|
Sign up to set email alerts
|

Interactive and Dominant Effects of Residues 128 and 141 on Cyclic Nucleotide and DNA Bindings in Escherichia coli cAMP Receptor Protein

Abstract: The molecular events in the cAMP-induced allosteric activation of cAMP receptor protein (CRP) involve interfacial communications between subunits and domains. However, the roles of intersubunit and interdomain interactions in defining the selectivity of cAMP against other cyclic nucleotides and cooperativity in ligand binding are still not known. Natural occurring CRP mutants with different phenotypes were employed to address these issues. Thermodynamic analyses of subunit association, protein stability, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Importantly, the comparison of the structure of effector (CO)-free CooA with that of effector (cAMP)-bound CRP (6) reveals a repositioning of these two C-helices with respect to each other, suggesting a role of this repositioning in the activation of these proteins in response to their respective effectors. Consistent with this concept, alterations of particular amino acids within the C-helices exert a variety of effects on the activity in CRP (12,13) and in the fumarate and nitrate reductase activator protein (14), another member of this transcriptional activator family. It is therefore our working hypothesis that CO binding to the heme of CooA alters the positioning of the C-helices and that this repositioning effectively transmits the effector-binding signal through the protein and leads to the reorganization of the DNA-binding domains.…”
mentioning
confidence: 69%
“…Importantly, the comparison of the structure of effector (CO)-free CooA with that of effector (cAMP)-bound CRP (6) reveals a repositioning of these two C-helices with respect to each other, suggesting a role of this repositioning in the activation of these proteins in response to their respective effectors. Consistent with this concept, alterations of particular amino acids within the C-helices exert a variety of effects on the activity in CRP (12,13) and in the fumarate and nitrate reductase activator protein (14), another member of this transcriptional activator family. It is therefore our working hypothesis that CO binding to the heme of CooA alters the positioning of the C-helices and that this repositioning effectively transmits the effector-binding signal through the protein and leads to the reorganization of the DNA-binding domains.…”
mentioning
confidence: 69%
“…On the other hand, the substitution of glycine in position 141 (with glutamine) causes the loss of CRP's ability to discriminate between cAMP and other cyclic nucleotides, although Gly141 is not involved in the interaction with cAMP and in the interaction between subunits [Cheng and Ching Lee, 1998]. …”
Section: Crp Activation Induced By Camp Bindingmentioning
confidence: 99%
“…Similar to that of effector-bound CRP, the structure of effector-free CooA indicated that a single ␣-helix (designated the C-helix) in each monomer serves to create the intersubunit dimerization domain (18). In CRP and FNR, alterations of particular amino acids in the center of this helix have a variety of effects on activity (25)(26)(27). In this report, we have identified CooA variants altered in the C-helix that have a perturbed ligation structure in the oxidized (Fe III ) form.…”
mentioning
confidence: 99%